Rancang Bangun Sistem Informasi Penjualan Bibits Buah Berbasis Framework Laravel - Fauzan, Muhammad; Hadiono, Kristophorus (Program Studi Teknik Informatika Universitas Pamulang, 2023)
In the business world, creativity is crucial to drive the growth of a business and provide it with a unique value compared to others. One form of creativity is the utilization of a website to expand the reach of product sales. This indirectly affects traditional fruit seedling businesses that rely on conventional methods to promote and sell their products. Moreover, the manual recording of sales and product data poses a risk of losing important information that may be needed at any given time. To address these issues, a website will be developed using the Laravel framework, one of the PHP programming languages. The data retrieval process will employ qualitative methods, while the system development will follow a prototype methodology. By utilizing the prototype methodology, the system development process will run smoothly and achieve the desired outcome, resulting in the creation of the desired application. With this web-based application in place, the fruit seedling business will be able to expand its reach while effectively managing critical data in an organized and secure manner.